Peran PAI dalam Mengatasi Mental Illness pada Usia Remaja - Putri Hidayah; Iskandar Yusuf (Syntax Idea)
This study aims to explore the role of Islamic Religious Education (PAI) in maintaining adolescents' mental health, specifically at SMP Negeri 25 Balikpapan. This research uses a qualitative descriptive approach with data collection techniques including observation, interviews, and documentation. The results of this study indicate that PAI activities, such as congregational prayers, dhikr, and teaching religious values, help adolescents cope with stress, anxiety, and depression. In addition, spiritual guidance provided by PAI teachers plays a significant role in shaping mentally and emotionally healthy character. Islamic Religious Education in schools not only serves as a medium for teaching religion but also as a means to strengthen adolescents' mental health through regular worship practices and the development of a spiritual relationship with God. This study concludes that strengthening the role of PAI in daily life can enhance adolescents' mental well-being and better prepare them to face life's challenges.